FEATURES OF FORMATION OF NATIONAL ETHNOPEDAGOGY AND EDUCATION COMPONENTS OF REPRESENTATIVES OF THE KAZAKH PEOPLE - Zhanabayev, D.K.; Abdikarimova, A.O. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2021)
The Kazakh people have a rich spiritual heritage, rooted in the depths of centuries, from the Orkhon-Yenisei ancient written monuments of the 6th-8th centuries to the present day. Kazakhstan is the land of eagle's wings. Kazakhstan, it occupies the territory from the shores of the Caspian Sea to the Altai Mountains, from the Ural Mountains to the high-mountainous Alatau in Semirechye. The Kazakhs have a saying: if the land is rich, then the people are also rich. Where the earth is full, life is generous. But unfortunately, this was not always the case, but the Kazakh people are residents of the CountryThe Great Steppe – from time immemorial had a huge single territory, and a single language, and a single national culture. The great son of the Kazakh steppe, an encyclopedic scientist, Aristotle of the East, Abu Nasr al-Farabi, was born on this land. Kazakh folklore is rich: all shades and nuances of folk pedagogy and folk psychology of nomads are concentrated in it. The invasions of Arabs, Mongols, Dzungars, which lasted almost ten centuries, destroyed the ancient Kazakh civilization. One Otrar tragedy, the heroic struggle of the inhabitants of this center of civilization of the Kazakh steppe, reminds of many things. A people whose culture has no.
Keywords: ethnopedagogy; national pedagogy; culture of the Kazakh people; components of education